Houellebecq, Pornographer? Monstration and the Remains of Sex. Issue 4 (8th August 2022) - Dutton, James
ABSTRACT: This article emerges from exhausted readings of controversial French novelist Michel Houellebecq's notorious portrayals of sex and sexuality to observe the relationship between the monstrous, the sexual, and extinction. Rather than dwell on what I call the "Houellebecq, pornographer" trope (that there are either too many, or too graphic, or too obscene depictions of sex in his novels), this article will observe Houellebecq's troubling of what sex might in fact be. This requires asking exactly what is meant, in terms of demonstration, by "sex" – especially in the literary setting of a novel, which, compared with the explicit potential different media have given to twenty-first century iterations of sexuality, is relatively tame. In doing so, I will ask exactly what is explicit about sexuality, especially considering its technical changes throughout modernity. I suggest that Houellebecq's attention to the depiction or de-monstration of sex, in all of its "monstrous" guises, comments on late-capitalist decadence and its extinctive trajectories – offering an ironic template from which to reconsider them.